2019
DOI: 10.1002/jcp.29312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a panel of mitotic spindle‐related genes as a signature predicting survival in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is one of the most malignant tumor types worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Previous research has confirmed that BUB1 could be viewed as a clinical biomarker for adverse prognosis and a potential therapeutic target in various tumours, 15,16 including aggressive colorectal cancer, 17 breast cancer 18 and glioblastoma 19 . Consistent with these studies, we showed that the overexpression of the BUB1 protein was associated with a poor response to chemotherapy and distant metastasis of OS.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has confirmed that BUB1 could be viewed as a clinical biomarker for adverse prognosis and a potential therapeutic target in various tumours, 15,16 including aggressive colorectal cancer, 17 breast cancer 18 and glioblastoma 19 . Consistent with these studies, we showed that the overexpression of the BUB1 protein was associated with a poor response to chemotherapy and distant metastasis of OS.…”
Section: Discussionsupporting
confidence: 89%
“…Although BUB1 seems to be a tumor suppressor, enhanced BUB1 expression causes chromosome instability and further induced oncogenesis [62]. Similar to CCNB2, BUB1 is also a hub protein in the NSCLC protein-protein interaction network and its overexpression is a poor prognostic indicator for NSCLC patients [59,63]. BUB1 inhibitors, in combination with taxanes or PARP inhibitors, could improve treatment efficacy and potentially overcome drug resistance [64].…”
Section: Discussionmentioning
confidence: 99%
“…BUB1, BUB1B, PLK1, and CDC20 were suggested as LUAD stem cell biomarkers (60). CENPF, KIF2C, CDK1, ASPM, and MYH10 were also proposed as diagnosis and prognosis biomarkers of LUAD (61)(62)(63)(64)(65)(66). CDKN3 was not yet reported as a diagnosis or prognosis biomarker but expected to be a promising therapeutic target in LUAD (63).…”
Section: Discussionmentioning
confidence: 99%